2018
DOI: 10.1080/02791072.2018.1438687
|View full text |Cite
|
Sign up to set email alerts
|

Tianeptine Abuse and Dependence in Psychiatric Patients: A Review of 18 Case Reports in the Literature

Abstract: Tianeptine is an atypical antidepressant approved in 25 countries for the treatment of depressive syndromes. Tianeptine abuse among psychiatric patients in the community and at inpatient wards has been increasingly reported in recent years. The purpose of this article is to alert clinicians to tianeptine abuse potential and identify any patterns in the literature. We searched the Academic Search Complete, Google Scholar, MEDLINE, Science Citation Index, Scopus, and the Social Sciences Citation Index for articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…2 Later, it was shown that tianeptine also modulates the glutamatergic system, showing effects on neuroplasticity in the hippocampus and amygdala. 3,4 In 2014, it was shown that tianeptine interacts with the opioid receptors µ and d. 5 Interaction with µ-receptors could explain the dependence issue in high doses, 6 while interaction with d-receptor could explain the antidepressant properties. 7 Tianeptine has a lateral amino acid chain that is directly associated with the pharmacological properties of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…2 Later, it was shown that tianeptine also modulates the glutamatergic system, showing effects on neuroplasticity in the hippocampus and amygdala. 3,4 In 2014, it was shown that tianeptine interacts with the opioid receptors µ and d. 5 Interaction with µ-receptors could explain the dependence issue in high doses, 6 while interaction with d-receptor could explain the antidepressant properties. 7 Tianeptine has a lateral amino acid chain that is directly associated with the pharmacological properties of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Also, intensified anxiety was present before alcohol problems began. These elements make tianeptine dependence diagnosis doubtful and indicate rather a personality predisposition to substance misuse, than a special addictive mechanism of tianeptine itself, as suggested in other publications 5,6 .…”
mentioning
confidence: 91%
“…Cases of intentional misuse have been documented going back as early as the 1990s in Europe (Vandel et al, 1999). Though typically prescribed at 12.5 mg 3 times daily, intentional misuse has been documented with doses ranging from 1500 mg to more than 4000 mg daily (Saatcioqui et al, 2006;Springer and Cubala, 2018). Intravenous use, with associated complications, has been reported (Vadachkoria et al, 2009;Ihan et al, 2013;Dempsey et al, 2017).…”
mentioning
confidence: 99%